Moral Behaviour of Adolescents in the Rural Community of Lithuania at the First Part of the Twentieth Century - Stonkuvienė, Irena (Acta Paedagogica Vilnensia, 2006)
Communication among contemporaries has crucial influence on the behaviour of adolescents. Communication flock them into specific associations, where they gain a unique psychological, social and moral experience. This experience is often different from that gained at communication with adults. In groups of contemporaries adolescents either adapt or deny moral virtues implanted by parents and other adults. Furthermore, qualities of adolescents, which are normally not demonstrated in front of parents, are disclosed. Negative influence of contemporaries is something that is specifically emphasized by parents and teachers. In various scientific studies (social, psychological, educological, etc.) groups of contemporaries are also often analysed as a factor having negative influence on moral behaviour of adolescents. Historical and ethnological data show that the problem of „group of contemporaries” is not something characteristic of our time only. This article, based on the material collected during ethnographic expeditions, analyses influence of group of contemporaries on moral behaviour of adolescents in the rural community of Lithuania at the first part of the twentieth century. Factors of grouping of contemporaries, activities of the groups, interrelations are discussed.
Keywords: moral behavior; adolescence; peer group; traditional culture